Tree of Pearls: The Extraordinary Architectural Patronage of the 13th-Century Egyptian Slave-Queen Shajar al-Durr (by D. Fairchild Ruggles) (American Journal of Islam and Society, 2023)
Almost any survey of medieval Islamic history will cover the figure of Shajar al-Durr (“Tree of Pearls” in Arabic), who was one of the fewwomen in Islamic history to hold the title of Sultan, and the only one to do so who began her life as a slave. She is also well known as a pivotal figure in Egyptian politics, as she marked the transition between Saladin’s Ayyubid dynasty (1171–1250 CE) and the Mamluk sultanate (1250–1517 CE). However, works that analyze Shajar al-Durr’s biography, reign, and influence often overlook her role as an architectural innovator. In Tree of Pearls, art historian D. Fairchild Ruggles highlights Shajar al-Durr’s architectural innovations and argues that her “architectural patronage…changed the face of Cairo and had a lasting impact on Islamic architecture”.